Group Therapy for Patients with Tinnitus at the University of Brasilia Medical School - Holdefer, Lisiane; de Oliveira, Carlos Augusto C.P.; Venosa, Alessandra Ramos (Brazilian journal of otorhinolaryngology, 2010)
Although group therapy for tinnitus is a well documented field in the international literature, as far as we know it has never been held in Brazil. This study represents a successful experience of a group therapy for tinnitus based on the tinnitus retraining therapy associated with behavioral cognitive techniques. The goal of the present study is to assess patients with tinnitus before and after the group therapy based on the tinnitus retraining therapy and the behavioral cognitive therapy. Prospective cohort study: 27 subjects signed in for the study, and answered the Tinnitus Handicap Inventory (THI) and the Hospital Depression and Anxiety Scale (HAD), before and after the treatment. We held six structured sessions according to the principles of tinnitus retraining therapy associated with behavioral cognitive techniques. 27 patients started and 19 finished the treatment (8 were taken off). 47.4% men, mean age of 47.6. THI results before and after treatment were respectively: functional: 29 and 14, emotional 24 and 10 and catastrophic 12 and 5 and the HAD scale: anxiety 2 and 9 and depression 10 and 6. The treatment described is effective in improving tinnitus symptoms.